PENGARUH EKSTRAK BUAH PEDADA PUTIH (Sonneratia alba) TERHADAP MORFOLOGI DAN VIABILITAS SPERMATOZOA MENCIT (Mus musculus) SEBAGAI SENYAWA ANTIFERTILITAS - Ainaya Salwa Fachrunnisa (2023)
Pedada fruit is a medicinal plant that has the potential as an alternative herbal contraceptive method that is safe, easy to obtain, and inexpensive. The metabolites compound such as flavonoids, saponins, and phenols in the fruit can affect the work of hormones, spermatogenesis process, and cause spermatozoa abnormalities. This study aims to assess the effect of pedada fruit extract on the quality of spermatozoa morphology and viability of mice (Mus musculus). This research uses complete randomized design (CRD) onto 30 male mice divided into 5 groups. K (-): 0.9% NaCl, K (+): 1% CMC, while treatment groups K3, K4, and K5 were each given 200, 300, 400 mg/KgBW of pedada fruit extract induced orally each day for 29 days. Data were analyzed using ANOVA with 95% confidence. The results showed that the administration of pedada fruit extract affected the morphology and viability of spermatozoa with p-value <0.05. Post hoc test result, showed the morphological variable results are meaningful while the viability variable is not meaningful. The conclusion is that the administration of pedada fruit extract (Sonneratia alba) at a dose of 200 mg/KgBW effectively reduces the morphological quality of mice spermatozoa and has the potential as a contraception.